MIT18 100BF10 Pset8sol

Download as pdf or txt
Download as pdf or txt
You are on page 1of 4

SOLUTIONS TO PS 8

Xiaoguang Ma

Solution/Proof of Problem 1. From f (x) = f (x2 ), we have


1 1 1
f (x) = f (x 2 ) = f (x 4 ) = · · · = f (x 2n ).
1
� 0, so lim yn = 1. Since f is continuous, we
Now let yn = x 2n , and assume x =
n→∞
have if x �= 0
f (x) = lim f (x) = lim f (yn ) = f ( lim yn ) = f (1).
n→∞ n→∞ n→∞

When x = 0, then f (0) = lim f (y) = f (1).


y→0
Then f is a constant.
Solution/Proof of Problem 2. From MVT, we have ∀x > 0, ∃y = y(x) ∈
(x, x + 1), s.t.
g(x) = f (x + 1) − f (x) = f � (y).
Notice that y > x, so lim y = ∞, so we have
x→∞

lim g(x) = lim f � (y) = 0,


x→∞ x→∞

since lim f � (y) = 0.


y→∞

Solution/Proof of Problem 3. Consider the function


C1 x2 Cn xn+1
g(x) = C0 x + + ··· + .
2 n+1
Then g(0) = 0 and g(1) = C0 + C21 + · · · + n+1
Cn
= 0. By the mean value theorem,

we have that g (y) = 0 for some y ∈ (0, 1), which means the equation C0 + C1 x +
· · · + Cn xn has a root between 0 and 1.
Solution/Proof of Problem 4. (a) Suppose f has two fixed point, x1 < x2 . Then
by MVT we have that
f (x2 ) − f (x1 )
∃y ∈ (x1 , x2 ), = f � (y).
x2 − x1
Then f � (y) = 1 which is a contradiction.
(b) If f has a fixed point, then
f (t) = t ⇒ t = t + (1 + et )−1 ⇒ (1 + et )−1 = 0.
But we know that et > 0 then (1 + et )−1 �= 0. So f has no fixed point.
(c)Consider a sequence defined by xn = f (xn−1 ) for any x1 ∈ R. Then we have
|xn − xn−1 | = |f (xn−1 ) − f (xn−2 )| = |f � (y)||xn−1 − xn−2 | � A|xn−1 − xn−2 |.
By using |x − z| � |x − y| + |y − z|, we have
� n−2


|xn −xm | � |xn −xn−1 |+|xn−1 −xn−2 |+· · ·+|xm+1 −xm | � Ai |x2 −x1 |.
i=m−1
1
2 SOLUTIONS TO PS 8

� i
Since A < 1, the series A converges, and so the partial sums form a Cauchy
sequence. This inequality shows that {xn } is also a Cauchy sequence and hence
converges.
Notice that |f (x + h) − f (x)| � Ah, so f is continuous. Then we have
x = lim xn = lim f (xn−1 ) = f ( lim xn−1 ) = f (x).
n→∞ n→∞ n→∞

So x is a fixed point of f (x).


Solution/Proof of Problem 5. f � (0) exists because of the following:
(0))�
By definition, f � (0) = lim f (x)−f
x
(0)
. Since we have (f (x)−f
(x)� = f � (x), and
x→0
f (x)−f (0)
the limit lim f � (x) = 3 exists, from L’Hospital rule, we know f � (0) = lim x
x→0 x→0
� f (x)−f (0)
exists and f (0) = lim x = 3.
x→0

Solution/Proof of Problem 6. From Taylor’s theorem, we have


1 (2)
f (x) = f (x0 ) + f � (x0 )(x − x0 ) + f (x0 )(x − x0 )2
2!
1 1
+ ··· + f (n−1) (x0 )(x − x0 )n−1 + f (n) (y)(x − x0 )n ,
(n − 1)! n!
for some y ∈ (x, x0 ) or (x0 , x). Then we have
1 (n) f (x) − f (x0 )
f (x) = f (x0 ) + f (y)(x − x0 )n ⇒ f (n) (y) = n! .
n! (x − x0 )n
We want to say that f (n) (y) has the same sign as f (n) (x0 ), but we have to be
careful because f (n) need not be continuous. It may well be the case that there is
a sequence zn approaching x0 such that f (n) (zn ) does not go to f (n) (x0 ). Never­
theless, we will show that if y(x) is the intermediate point in (x, x0 ) appearing in
Taylors’s theorem, then as x → x0 , f (n) (y) → f (n) (x0 ).
The reason is that, as pointed out above,
f (x) − f (x0 )
lim f (n) (y) = lim n! ,
x→x0 x→x0 (x − x0 )n
and we can compute the limit on the right by using L’Hôpital’s rule n − 1 times:
f (x) − f (x0 ) f � (x) f (n−1) (x)
lim n! = lim (n − 1)! = . . . = lim
x→x0 (x − x0 )n x→x0 (x − x0 )n−1 x→x0 (x − x0 )

and then noticing that since f (n−1) (x0 ) = 0, this is equal to


f (n−1) (x) − f (n−1) (x0 )
lim = f (n−1) (x0 ) = A
x→x0 (x − x0 )

If A > 0, then f ((xx)−f (x0 )


−x0 )n > 0 in a neighborhood of x0 . If n even, this implies
f (x) − f (x0 ) > 0 for any element in the neighborhood of x0 , i.e x0 is a local
minimum. When n is odd, f does not have a local minimum or maximum.
Similarly, if A < 0 and n even, then f (x) − f (x0 ) < 0 for any element in the
neighborhood of x0 , i.e x0 is a local maximum. When n is odd, f does not have a
local minimum or maximum.
SOLUTIONS TO PS 8 3

Solution/Proof of Problem 7. For x > 0 we have f (x) = x3 and hence f � (x) =


3x2 and f �� (x) = 6x. For x < 0 we have f (x) = −x3 and hence f � (x) = −3x2 and
f �� (x) = −6x. Notice that we can write, for x �= 0,
f (x) = |x|x2 , f � (x) = 3|x|x, f �� (x) = 6|x|.
Hence at x = 0 we have
f (h) − f (0) |h|h2
f � (0) = lim = lim = lim |h|h = 0
h→0 h h→0 h h→0

�� f � (h) − f � (0) 3|h|h


f (0) = lim = lim = lim 3|h| = 0
h→0 h h→0 h h→0
�� ��
f (h) − f (0) 6|h|
f ��� (0) = lim = lim does not exist
h→0 h h→0 h
MIT OpenCourseWare
http://ocw.mit.edu

18.100B Analysis I
Fall 2010

For information about citing these materials or our Terms of Use, visit: http://ocw.mit.edu/terms.

You might also like